If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -19 + 3x + 6 + 2x + -10 = 180 Reorder the terms: -19 + 6 + -10 + 2x + 3x + 2x = 180 Combine like terms: -19 + 6 = -13 -13 + -10 + 2x + 3x + 2x = 180 Combine like terms: -13 + -10 = -23 -23 + 2x + 3x + 2x = 180 Combine like terms: 2x + 3x = 5x -23 + 5x + 2x = 180 Combine like terms: 5x + 2x = 7x -23 + 7x = 180 Solving -23 + 7x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 7x = 180 + 23 Combine like terms: -23 + 23 = 0 0 + 7x = 180 + 23 7x = 180 + 23 Combine like terms: 180 + 23 = 203 7x = 203 Divide each side by '7'. x = 29 Simplifying x = 29
| 17k^2+119k=0 | | 9a-4=14 | | 4x=5y+6 | | A/6=-18 | | -3+9=-21 | | 2a+x=7 | | 3x+(-15+3x)=21 | | 8x-52=x | | 11x-9=8x+6 | | 9g^2+g=0 | | -7/3(y-12)-1/9y | | C-7.2=12 | | 3x^2+36x-8=0 | | 3x^2=19x+14 | | 13=-2+c | | y=ln(x^4+e^2x) | | 4*sin*2x-1=-5 | | -4b^2+81=0 | | 3(20+h)=1 | | f(x)=ln(x^4+e^2x) | | -24=-10a | | p=2m+n | | 2x-(-x+5)=6+(x+1) | | 11=h+3 | | 43o+8+6o=-90 | | 2(50-x)=40 | | -4=y/5 | | -25x-17=12x-8 | | X(5x-1)+5=5x(x-5)+x | | 6+4+f+f+2= | | 8z-5=73+2z | | 6x=74 |